The Use of Platelets-Rich Fibrin (PRf) to Accelerate Healing Process After Tooth Extraction and Dental Implants - Aminzouhori, Mohammad; Alhazzaa, Ahmad Alkhalaf; Sharshenidze, Megi (Caucasus Journal of Health Sciences and Public Health, 2020)
Postoperative wound healing is an important stage that cannot be ignored. The literature contains relatively limited informations about disturbed wound healing , and there is no acceptable description about wound healing process in oral cavity. Wound healing contains a sequence of complex biological processes , All tissues alike follow a similar essential pattern to complete the healing process . Generally, we have two main types of tissues included in surgery of oral cavity , soft tissue (gum) and hard tissues (jaws bones), each one of them has it’s own requirements to complete the process of healing , And each of them requires a certain time also to be fully recovered. By Focusing on the time required to recover, in this research we are going to discuss a new method (Platelets Rich Fibrin) to accelerate wounds healing process mainly after 3rd molar extraction and after an implant fixation to the jaws bones . Platelet rich fibrin (PRF) is a fibrin matrix in which platelet cytokines, growth factors, and cells are trapped and may be released after a certain time and that can serve as a resorbable membrane.